2020
DOI: 10.1016/j.cub.2020.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Effects of Brassinosteroid Perception in Developing Phloem

Abstract: Highlights d BR perception in developing phloem rescues the dwarfism of receptor mutants d BR perception antagonizes CLE45 peptide signaling in the root protophloem d Local and systemic effects of BR perception in the phloem are genetically distinct d Developing phloem can orchestrate cellular behavior of adjacent tissues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 81 publications
(158 reference statements)
3
68
0
1
Order By: Relevance
“…However, pSHR-BRI1 has a shorter root and wide meristem that largely rescued these defects. A tissue-specific approach also assisted in separating BRI1 control of phloem differentiation from that of growth (Graeff et al, 2020). Since BRI1 is not expressed in the phloem in the lines analysed here, restoration of BR signalling in diverse cell types is sufficient to control root length and orientation of transversal walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pSHR-BRI1 has a shorter root and wide meristem that largely rescued these defects. A tissue-specific approach also assisted in separating BRI1 control of phloem differentiation from that of growth (Graeff et al, 2020). Since BRI1 is not expressed in the phloem in the lines analysed here, restoration of BR signalling in diverse cell types is sufficient to control root length and orientation of transversal walls.…”
Section: Discussionmentioning
confidence: 99%
“…However, formative divisions are promoted by BRI1 in the stele and restrained by epidermal BRI1 (Kang et al, 2017). In addition, BRI1 activity in the protophloem cells of the vasculature can rescue the bri-triple root phenotype (Graeff et al, 2020; Kang et al, 2017). Together, tissue-specific approaches revealed that growth control by BRI1 involves cell autonomous and non-cell autonomous effects.…”
Section: Introductionmentioning
confidence: 99%
“…CLE45 was shown to be perceived by RECEPTOR LIKE PROTEIN KINASE 2 to regulate PSE identity by maintaining a plastic zone in the root meristem zone where the cell identities of PSE and PSE-adjacent companion cells are interchangeable, which is important for the formation of a functional phloem [88]. Interestingly, CLE45 signaling is locally antagonized by protophloem-specific BR perception to allow protophloem differentiation, which may trigger an unidentified phloem-derived mobile signal to rescue the dwarfism and patterning defects in bri1;brl1;brl3 triple mutants [89]. CLE26 also represses protophloem development as well as primary root growth [90,91].…”
Section: Open Accessmentioning
confidence: 99%
“…It is possible that RPK2 also interacts with BAM3 or CLV2/CRN for sensing the CLE45 signal to suppress phloem identity. Most recently, it was reported that the bri1 brl1 brl3 triple mutants display defective protophloem differentiation and are slightly hypersensitive to CLE45 treatment, which can be rescued by bam3 mutation or phloem-specific BRI1 expression, indicating that the CLE45-BAM3 signaling in regulating protophloem differentiation is also modulated by brassinosteroid perception (Kang et al 2017;Graeff et al 2020).…”
Section: Rlk-mediated Signaling Promotes the Differentiation Of The Pmentioning
confidence: 99%